2021
DOI: 10.1088/1361-6463/abf44a
|View full text |Cite
|
Sign up to set email alerts
|

Charge trap spectroscopy in polymer dielectrics: a critical review

Abstract: Trapping phenomena are essential features controlling the transport properties of insulating materials. Depending on the energy depth, traps can either assist transport or lead to long-lasting storage of charges. The consequences of charge trapping are non-linear phenomena and electric field distribution distortion in the dielectric bulk. The important characteristics about traps are the nature of the levels, their depth in energy, and their density. In this review, we discuss the different techniques availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 233 publications
(392 reference statements)
1
34
0
Order By: Relevance
“…The analysis of TSDC peak poses the problem of solving the case of distributed processes. Different results showed that in presence of a distribution of trap depths, an underestimate of the activation energy is obtained [1]. However, in general, energies found in TSDC tend to match those found in isothermal decay.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The analysis of TSDC peak poses the problem of solving the case of distributed processes. Different results showed that in presence of a distribution of trap depths, an underestimate of the activation energy is obtained [1]. However, in general, energies found in TSDC tend to match those found in isothermal decay.…”
Section: Discussionmentioning
confidence: 91%
“…Different methods have been implemented over the years to get insight into fundamental properties of traps that are the physical-chemical nature, the energy depth, and the amount. Methods can be with or without stimulation of charge detrapping and are based on either pure electrical response such as surface potential decay, coupled thermal-electrical effects as with thermally stimulated discharge current (TSDC) or couple electrical-optical effects as in photostimulated discharge (PSD) for example, as reviewed recently [1].…”
Section: Introductionmentioning
confidence: 99%
“…The fact that polymers exhibit complex TSDC spectra comprising of several overlapping of (quasi-) continuous trap bands-along with the TSDC polarity reversal effect observed in the deep trap region in Figure 9a-complicate the analysis and evaluation of trapping parameters (trap depth and density of occupied states) as discussed in detail elsewhere 86,88 . Due to these reasons we do not attempt e.g.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…Due to these reasons we do not attempt e.g. peak-fitting 86 , deconvolution 89,90 or numerical methods 91,92 to derive trap parameters here, as the results would be largely inconclusive 88 . Nevertheless, the TSDC results presented herein clearly indicate a modification of trap density of states (DOS) and a more homogeneous distribution of charge in the silica-containing samples, and the results are consistent with the PEA space charge depolarization behavior measured from the nonoriented cast films (Figure 4), thereby confirming the modification of charge trapping properties also in silica-BOPP thin films.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…Since all residues result from resists and, hence, are insulating, they affect the work-function of graphene by the formation of interface dipoles [24][25][26][27] or by trapped charges. 28 Dipoles from residues on top or below graphene are known to locally dope graphene. 29 This has been evidenced, e.g., via intentionally preparing self-assembled polymer films on the substrate prior to graphene deposition.…”
Section: Induced Electric Field Mapsmentioning
confidence: 99%